Children and the law in the Netherlands: a comparative introduction - Weijers, Ido (Eleven International Publishing, 2018)
"This book gives a very brief introduction to the extensive field of Dutch juvenile law. It offers a concise account of some of the most relevant and most typical points in various legal fields, including aspects of child protection and juvenile justice, as well as features of family law such as parenthood, minority and parental authority, youth care and migration law. Various Dutch laws and regulations that are relevant to children are compared to corresponding laws and regulations in other countries."--Back cover